The Integrity Crisis of State Apparatus: A Criminal Law Study of Systemic Corruption Practices - Gussman, Angga Aldilla (Ipso Jure, 2026)
Corruption, as an extraordinary crime, has developed into a systemic practice that threatens the integrity of state officials and weakens governance. The main problem in eradicating corruption lies not only in law enforcement but also in normative weaknesses, particularly the vagueness of norms regarding the element of "abuse of authority." This study aims to analyze how the vagueness of norms in criminal law on corruption contributes to the development of systemic corruption and its implications for the integrity crisis of state officials. The research method used is normative legal research with a statutory, conceptual, and case-based approach, through an analysis of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 as well as related doctrines and court decisions. The results show that the vagueness of norms regarding the element of abuse of authority gives rise to multiple interpretations in judicial practice, which has implications for disparate decisions, inconsistent law enforcement, and the emergence of the phenomenon of policy criminalization and impunity. This condition weakens the effectiveness of corruption eradication and is unable to create an optimal deterrent effect. Furthermore, these substantive weaknesses in the law are correlated with the weak integrity of state officials within the judicial system, thus reinforcing the systemic nature of corruption. Therefore, a reformulation of criminal law norms on corruption is needed that is firmer and more in harmony with administrative law, as well as strengthening the integrity of state officials to achieve legal certainty, justice, and legal benefits in eradicating corruption.